De la «analogia entis» a la «analogia incarnationis»: Nuevas mediaciones de razón para una propuesta cristológica - Bacas, Serafín Béjar (Estudios eclesiásticos, 2022)
Christology aims to universalize the evangelical narrative. For this they are necessary certain mediations of reason that make this task possible. The author of this article, inspired by contemporary phenomenology, proposes as valid mediations the «manifestation», the «flesh» and the «gift» in order to devise a Christological proposal of a Trinitarian nature. In this way, Christology would abandon the hegemony of the thought of being (analogia entis) to open up to a new horizon characterized by the thought of appearing (analogia incarnationis).